Wearable Computing : From Modeling to Implementation of Wearable Systems based on Body Sensor Networks - Fortino, Giancarlo, 1971- ?UNAUTHORIZED; Gravina, Raffaele, 1982-; Galzarano, Stefano, 1984- (Hoboken, NJ : John Wiley & Sons, 2018)
Includes bibliographical and references